Full journal publication of abstracts presented at the Nordic Congress of General Practice in 2009 and 2011 - Frans Boch Waldorff; Kristine Petersen; Siri Vinther; Håkon Sandholdt; Volkert Siersma; John Sahl Andersen (Taylor & Francis Group, 2017)
Objective: To determine the overall publication rates for abstracts presented at two consecutive Nordic Congresses of General Practice and to evaluate determinants for these publication rates. Design: Prospective study. Setting: MEDLINE (PubMed) and Google Scholar were searched for relevant publications from 1 January 2009 up until 31 August 2014. Methods: Abstracts accepted for oral or poster presentation were identified from the original congress booklets from the Nordic Congresses of General Practice in 2009 and 2011. Based on PubMed and Google Scholar searches, we subsequently identified full journal publications within a 36-month follow-up from both congresses. In cases of doubt, the first author was contacted directly. Main outcome measures: Full journal publication within 36 months after the congress. Results: A total of 200 abstracts were analyzed. Of these, 85 (42.5%) were identified with a full publication within 36 months after the congress. More abstracts from the 2011 congress were published compared to the 2009 congress odds ratio (OR) 1.97, 95% confidence interval (CI) (1.10; 3.50). Abstracts accepted for oral presentation were more often published OR 1.94, 95% CI (1.08; 3.50) than accepted poster abstracts. In the multivariate analysis, a university affiliation for both first and last author increased the probability for publication OR 4.23, 95% CI (1.71; 10.42), as well as more than two authors. An optimal number, based on the highest OR, seems to be 3-4 authors with OR 2.43, 95% CI (1.07; 5.54). Qualitative studies were published at the same frequency as quantitative studies OR 1.36, 95% CI (0.57; 3.24). Conclusion: Less than half of the abstracts accepted for oral or poster presentation at two consecutive Nordic Congresses of General Practice were published as full text articles within 36 months. Key points Congress abstracts accepted for Nordic Congress of General Practice are not indexed in international search databases. Less than half of the abstracts accepted for oral or poster presentation at two consecutive Nordic Congresses of General Practice were published as full text articles within 36 months. Future congress committees could address this aspect in order to increase the visibility of and accessibility to research within the field of general practice.